Plan estratégico turístico del cantón Bolívar, provincia de Manabí - Cedeño Basurto, Jairo Javier (2012)
The thesis entitled "Strategic Plan Bolivar Canton Tourism, Province of Manabí" had as its object of study to the district Bolivar in the province of Manabí, whose overall objective was to design a strategic plan for tourism development Bolivar county to ensure sustainability and good living of the population. Specific objectives were established to diagnose situation, SWOT analysis, formulating strategies for action and identifying programs and projects of the strategic plan. Diagnosis was obtained by concrete and specific data on the tourism situation in the canton Bolivar and developed a register of establishments providing tourism services. SWOT analysis allowed the identification of problems and formulating action strategies were developed by which programs and projects. Finally concluded that it is necessary to implement the strategic plan as it will improve the tourism industry and position has a tourist destination with quality services.